Race and Gender Discrimination in Bargaining for a New Car - Ayres, Ian; Siegelman, Peter (American Economic Review, 1995)
More than 300 paired audits at new-car dealerships reveal that dealers quoted significantly lower prices to white males than to black or female test buyers using identical, scripted bargaining strategies. Ancillary evidence suggests that the dealerships' disparate treatment of women and blacks may be caused by dealers' statistical inferences about consumers' reservation prices, but the data do not strongly support any single theory of discrimination.